Perancangan Aplikasi Augmented Reality Media Pembelajaran Pengenalan Monumen Nasional Berbasis Android Menggunakan Sdk Vuforia - Alwi Alfisyahri (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2025)
The development of information and communication technology has significantly contributed to innovations in educational media, one of which is the use of Augmented Reality (AR). AR is a technology capable of combining virtual objects with the real environment in real-time, thereby enhancing students’ engagement and understanding of learning materials. This research aims to design an Android-based Augmented Reality application as an interactive learning medium for introducing the National Monument (Monas) by utilizing the Vuforia Software Development Kit (SDK). The research method consists of several stages, including needs analysis, design, implementation, and testing. The needs analysis focused on identifying learning materials about Monas, including its main parts, historical background, and symbolic values. In the design stage, an interactive multimedia development model was applied by integrating 3D objects of Monas, informational texts, and audio explanations. The application was implemented using Unity 3D as the game engine combined with Vuforia SDK for marker recognition and 3D object rendering. The testing results indicate that the application can detect markers stably, display a detailed 3D model of Monas, and provide users with comprehensible educational information. A limited trial conducted with a group of students revealed increased learning motivation and understanding of the National Monument, as the interactive and visual-based presentation was more engaging compared to conventional media. Therefore, this Android-based Augmented Reality application for Monas recognition can serve as an innovative, effective, and technology-driven learning medium that creates a more enjoyable and meaningful learning experience.